2018
DOI: 10.3928/19382359-20181022-02
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Liver Diseases in Children

Abstract: Autoimmune liver disease remains difficult to diagnose, and distinguishing the various causes is difficult as well. In children, it can present with wide variation, including autoimmune hepatitis (AIH), primary sclerosing cholangitis (PSC), and the “overlap syndrome” of AIH/PSC, also known as autoimmune sclerosing cholangitis. These liver disorders are thought to be immune-mediated, but their etiology remains unclear. They are not secondary to inherited or acquired diseases and they are not associated with any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We found the AIH type-1 (positive anti ANA) as a commonest cause of CLD, was diagnosed by combination of clinical picture, laboratory work up and typical liver histology in the absence of a particular cause. 5 The study conducted by Hanif et al 3 also showed that in their group of children of CLD, viral hepatitis B followed by Wilson disease were the commonest diseases. Another study performed in Pakistan revealed the hepatitis C and glycogen storage disease were the top two diseases in the list of their group of children.…”
Section: Discussionmentioning
confidence: 96%
“…We found the AIH type-1 (positive anti ANA) as a commonest cause of CLD, was diagnosed by combination of clinical picture, laboratory work up and typical liver histology in the absence of a particular cause. 5 The study conducted by Hanif et al 3 also showed that in their group of children of CLD, viral hepatitis B followed by Wilson disease were the commonest diseases. Another study performed in Pakistan revealed the hepatitis C and glycogen storage disease were the top two diseases in the list of their group of children.…”
Section: Discussionmentioning
confidence: 96%
“…AIH is characterized biochemically by high level of transaminase, histologically by the presence of interface hepatitis, and serologically by a high level of immunoglobulin G (IgG) [1][2][3][4]. AIH is further subdivided into type I and type II, depending on the autoantibody profile: AIH type I is characte-rized by positivity for the anti-nuclear antibody (ANA) and/or anti-smooth muscle antibody (ASMA), and AIH type II is characterized by the presence of anti-liver kidney microsomal antibody type I (anti-LKM1) and/or anti-liver cytosol type 1 [5][6][7][8][9]. Overlap syndrome describes variant forms of AIH, which includes features of a combination of AIH, primary sclerosing cholangitis, and primary biliary cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…procedure with risk of complications [3][4][5][6][7]. Limited studies discuss the role of shear-wave elastography, magnetic resonance (MR) elastography, and MR spectroscopy in the diagnosis and monitoring of patients with AIH, but these results are preliminary and overlapping [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations